A Combined Histone Deacetylases Targeting Strategy to Overcome Venetoclax Plus Azacitidine Regimen Resistance in Acute Myeloid Leukaemia: Three Case Reports - Wang, Bin-Ru; Wan, Chao-Ling; Liu, Song-Bai; Qiu, Qiao-Cheng; Wu, Tian-Mei; Wang, Jun; Li, Yan-Yan; Ge, Shuai-Shuai; Qiu, Yan; Shen, Xiang-Dong; Xue, Sheng-Li; Li, Zheng (Frontiers in Oncology, 2021)
The management of patients with relapsed or refractory (R/R) acute myeloid leukaemia (AML) remains a challenge with few reliably effective treatments. Chidamide, a new selective HDAC inhibitor, has demonstrated some effectiveness in AML patients. Herein, we reported three patients with R/R AML who were unresponsive to venetoclax plus azacitidine (VA) but were successfully treated with VA when chidamide was added to the regimen. MCL1 is one of the anti-apoptotic proteins. Chidamide targets the MCL1 protein, which may permit venetoclax resistance when upregulated. We determined MCL1 protein expression in different AML cell lines, and chidamide could downregulate MCL1 expression in venetoclax resistance AML cells. In general, our experience showed that the chidamide/VA combination could improve the condition of R/R AML patients who are resistant to VA. Formally evaluating this regimen in R/R AML patients may be meaningful.